An Empirical Application of Laboratory Experimental Auctions in Marketing Research - Dale J. Menkhaus; George W. Borden; Glen D. Whipple; Elizabeth Hoffman; Ray A. Field (Journal of Agricultural and Resource Economics, 1992)
A laboratory experimental auction was used to determine factors influencing the relative value consumers place on alternative retail beef packaging. Results indicate information is very important for the successful introduction and marketing of the vacuum skin package. Physical appearance of the beef plays a major role in purchasing decisions by consumers, with fat and shape significantly decreasing the value of beef in the vacuum skin package relative to beef in the overwrapped styrofoam tray package. Experimental economics procedures, when combined with traditional marketing research techniques, can provide useful information for marketing decisions and economic analyses.